2007
DOI: 10.1074/jbc.m700551200
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Catalysis of Escherichia coli ATP Synthase F1 Sector

Abstract: A similar approach was taken for mutations in the ␤ subunit key region; consistent with its bulk phase ATPase activities, F 1 with the Ser-174 to Phe substitution (␤S174F) exhibited a slower single revolution time (time required for 360 degree revolution) and paused almost 10 times longer than the wild type at one of the three 120°positions during the stepped revolution. The pause positions were probably not at the "ATP waiting" dwell but at the "ATP hydrolysis/product release" dwell, since the ATP concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…In contrast, the pause duration before the 40°rotation step was modulated by the slow hydrolysis rate of ATP␥S 2 or by the catalytic site mutant ␤E190D (in the Bacillus PS3 F 1 ), which was found to significantly increase the length of the catalytic dwell (20). These data together indicate that the dwell before the 40°step is the "catalytic dwell" (20) and defines the order of the substeps during the 120°rotation step observed in high Mg⅐ATP concentrations (21).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…In contrast, the pause duration before the 40°rotation step was modulated by the slow hydrolysis rate of ATP␥S 2 or by the catalytic site mutant ␤E190D (in the Bacillus PS3 F 1 ), which was found to significantly increase the length of the catalytic dwell (20). These data together indicate that the dwell before the 40°step is the "catalytic dwell" (20) and defines the order of the substeps during the 120°rotation step observed in high Mg⅐ATP concentrations (21).…”
mentioning
confidence: 67%
“…Furthermore, the free Mg 2ϩ concentration is relatively low (Ͻ0.4 mM) to reduce its inhibitory effects (38). The beads occasionally exhibited long pauses (Ͼ0.1 s), which play a role in the bulk steady state ATPase activity (21) (also see below). They were not considered in the present study because we are only analyzing the partial reactions of continuous rotational catalysis, which includes the ratelimiting step.…”
Section: Direct Observation Of Rotation Using a 60-nm Gold Beadmentioning
confidence: 99%
“…These results suggested that approximately 10% of the F 1 molecules were rotating at the milliseconds time resolution. This interpretation became more convincing on observing longer time courses of randomly selected beads (Nakanishi-Matsui et al His-tag glass When the beads were followed for a longer time, we observed that they unexpectedly paused sometimes for longer than 0.1 s, possibly due to MgADP inhibition (Nakanishi-Matsui et al 2007). Longer pause of single beads should certainly lower the steady-state ATPase, which corresponds to the average rate of randomly selected beads.…”
Section: (B) Stochastic Rotationmentioning
confidence: 82%
“…Thus, the rotation pauses before the 808 step, when the ATP concentration was lowered. The 1208 steps observed with a higher ATP concentration most probably reflected ATP hydrolysis/product release (Nakanishi-Matsui et al 2007). …”
Section: Rotational Catalysis Of F-atpasementioning
confidence: 99%
See 1 more Smart Citation